Fashion and beauty advertising models’ age and its impact on over 50 female consumers’ purchase intention - Pereira, H.; Salgueiro, M. F. (2019 Global Fashion Management Conference at Paris Proceedings, 2019)
Introduction The study aims to collaborate to a better understanding of a social phenomenon that has gained increasing importance and analyze it under a commercial perspective, concluding about the impacts that it can bring for some markets. The purpose is to study the impact of the Fashion and Beauty advertisements models’ age on the purchase intention of female consumers over 50. This is a segment that has been gaining weight, expression and importance, and it is crucial to understand if it is been addressed with an effective communication strategy.